Formal contracts, relational contracts, and the holdup problem - Hideshi Itoh; Hodaka Morita (Center for Economic Studies and ifo Institute (CESifo), 2006)
We study the holdup problem in repeated transactions between a seller and a buyer such that the seller makes relation-specific investments in each period. We show that where, under spot transaction, formal contracts have no value because of the cooperative nature of investment, writing a simple fixed-price contract can be valuable under repeated transactions: There is a range of parameter values in which a higher investment can be implemented only if a formal price contract is written and combined with a relational contract. We also show that there are cases in which not writing a formal contract but entirely relying on a relational contract increases the total surplus of the buyer and the seller. The key condition is how the investment affects the renegotiation price in general, and the alternative-use value in particular.
Keywords: D23; L14; L22; L24; 330